Keberterimaan Kelompok Tani Hutan pada Pembangunan Kesatuan Pengelolaan Hutan di KPH Yogyakarta dan KPH Wilayah IX Panyabungan - Secunda Selamet Santoso; Dodik Ridho Nurrochmat; Bramasto Nugroho; Iman Santoso (Jurnal Penyuluhan, 2019)
This study aims to explain acceptance of the FFG towards FMU development based on their perception and the participation level. The research located in Special Region of Yogyakarta (SRY)and North Sumatera Province who had difference of the FMU’s level organization maturity, then selected three FFG who located at FMU Yogyakarta, and four FFG at FMU Regional IX Panyabungan, North Sumatera Province. Variables were compared by ordinal number and Likert scale. Rank Spearman correlation test (Rs) used to found relation between variables. The results showed the acceptance of the FFG was quite good based on a good perception of the FMU Region IX Panyabungan’s existence of 97.70%, and in FMU Yogyakarta which was only 76.38%. However, the perception of the benefits received from community empowerment  was dominated by the perception that no benefit was 59.77% in FMU Wilayah IX Panyabungan, and the perception in FMU Yogyakarta that it had benefited 54.3%. The perception of community empowerment towards the level of participation in FMU Region IX Panyabungan had a weak correlation, while in FMU Yogyakarta had a strong and direct correlation to the perception of the FMU’s existence. The level of participation was reflected that the maturity of the FMU organization along with the stability of FFG showed a strong enough correlation with the internal characteristics of FFG members. The Arnstein’s level of the FFG’s participation in FMU Region IX Panyabungan enters the level of tokens, while in FMU Yogyakarta reachs the degree of citizen power.